Pressure- and Temperature-Dependent Viscosity Measurements of Lubricants With Polymeric Viscosity Modifiers - LotfizadehDehkordi, Babak; Shiller, Paul J.; Doll, Gary L. (Frontiers in Mechanical Engineering, 2019)
The pressure–viscosity coefficient, α, is a measure of the pressure dependence of the viscosity of the liquid in elastohydrodynamic lubrication (EHL). There seems to be confusion around the understanding of the pressure–viscosity response in the inlet zone. In this paper the values of α were obtained from measurements of viscosity as a function of pressure and offers a understanding on the piezoviscous effect at various inlet pressures for those liquids. Moreover, the viscosities of several commercial engine oils and laboratory blends of mineral and synthetic base oils with polymer additives were measured at pressures up to 1 GPa and at temperatures of 40°C, 75°C, and 100°C. It was observed in some of these materials The significant changes within viscosity are temperature- and pressure-dependent. Analysis of the experimental results indicated that the solidification (significant increase viscosity) is due to liquid-solid phase transitions occurring in the lubricant’s polymer additives. Thus, this paper gives evidence on the role of molecular weight and concentration of polymer and its influence on the pressure- and temperature-dependent onset of the phase transitions. This transition has not been discussed in the open literature and is not accounted for in current bearing design using the Barus equation or the modified Yasatomi equation and may be the cause of some bearing damage modes.